2007
DOI: 10.1509/jmkg.71.4.140
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Consumer Contests

Abstract: A consumer contest is a sales promotion technique that requires participants to apply certain skills as they compete for prizes or awards. This article is the first to employ a game-theoretical approach to investigate consumer contest design issues, including prize structure, segmentation, and handicapping. First, the authors find that both skill distribution and the number of contestants play an important role in determining the optimal prize structure in consumer contests. Specifically, if the skill distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…The extant literature has focused extensively on contest design [10,40,61,65] or the effects of individual behavior on contest outcomes with the goal of maximizing the payoff [1,6,32,46,64]. These studies have demonstrated the advantages of crowdsourcing, such as lower cost [32], lower risk [10], higher quality solutions [24], and multiple alternative solutions [61].…”
Section: Conference On Information Systems Best Research-in-progressmentioning
confidence: 99%
“…The extant literature has focused extensively on contest design [10,40,61,65] or the effects of individual behavior on contest outcomes with the goal of maximizing the payoff [1,6,32,46,64]. These studies have demonstrated the advantages of crowdsourcing, such as lower cost [32], lower risk [10], higher quality solutions [24], and multiple alternative solutions [61].…”
Section: Conference On Information Systems Best Research-in-progressmentioning
confidence: 99%
“…Deci, 8 for example, found that an individual ' s need for competence would lead them to seek challenges that were aligned with or just above their capabilities. More generally, Liu et al 11 found that an alignment of skills had a positive effect on contest engagement, leading to increased performance.…”
Section: Understanding Contest Engagementmentioning
confidence: 99%
“…The winner of a contest is selected by judging the quality of their entry against all other entries. 11,12 Contests can take on a single-stage or multi-stage design. In a single-stage design, a contestant enters, competes and wins or loses in a single contest round.…”
Section: Consumer Contestsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results discussed below are based on a particular case of the general framework presented in the previous section (Liu, Geng, and Whinston, 2004). In particular, we maintain that users differ in their ability levels, but their performance is a deterministic function of usage and ability.…”
Section: Design Issuesmentioning
confidence: 99%